Behaviour of displacement, cast-in-place piles on collapsible soil - Ferreira, C. V.; Lobo, A. S.; Carvalho, D. (A A Balkema Publishers, 1997)
The paper presents the results of instrumented compression load tests carried out in three uncased cast-in-place piles (pounded piles, called apiloadas in Brazil) which is largely used in interior part of the state of São Paulo. The tests were conducted with the soil in the natural condition and after soaking with water, before loading, in order to evaluate the influence of the soil collapsibility in the results. The values of the ultimate loads (total, point and lateral loads) obtained in the tests are presented and compared with the values predicted by empirical methods that utilize SPT and CPT results.